Marmet technique and oxytocin massage increase the smoothness of breastfeeding - Burhan, Rialike; Mizawati, Afrina; Mariati, Mariati; Asmariyah, Asmariyah; Nurcahyani, Lia (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2023)
Background: Breast milk is the best baby food and every baby has the right to get breast milk. Based on data from the World Health Organization (WHO) in 2018, data on the coverage of exclusive breastfeeding in several countries had not yet reached the target. Referring to the national target of 80%, in 2018 nationally the coverage of babies receiving exclusive breastfeeding is 68.74%. Meanwhile, in Bengkulu province, newborns who received exclusive breastfeeding were 65.46%. Based on the results of the 2018 Riskesdas, the proportion of breastfeeding patterns for infants aged 0-5 months in Indonesia is 37.3% exclusive breastfeeding.Objectives: This study aimed to determine the effectiveness of the marmet technique and oxytocin massage on the smoothness breastfeeding .Methods: This research used a quantitative approach with a quasi-experimental design, employing a two-group pretest-posttest design with a control group. The experimental group was administered the Marmet technique, while the control group received oxytocin massages for seven consecutive days. The sample for this study consisted of 60 first-day postpartum mothers, with 30 in the intervention group and 30 in the control group. The research was conducted at PMB Bengkulu City. The research instruments used observation sheets, and data analysis was tested using the t-test and processed using computerization. Results: The statistical results obtained showed that there was a significant difference between the groups given the marmet technique and oxytocin massage regarding the smoothness of breast milk, where the marmet technique group had better improvement. There is a relationship between education and parity with breastfeeding fluency but there is no relationship between age and work with breastfeeding fluency. Intervention and parity variables are the most effective variables in increasing the smooth breastfeeding of postpartum mothers.Conclusions: There is an effect of the marmet technique and oxytocin massage on the smoothness of breast milk. It is expected that midwives can provide midwifery care for postpartum mothers by applying the marmet technique and oxytocin massage for the smooth production of breast milk and can be disseminated to the community